Technological Innovation and Sustainable Development in Africa-Europe Agribusiness Collaboration: A Framework for Modern Agricultural Transformation - D’Orazio, Nicola (Digital Repository of Theses - SSBM Geneva, 2025)
Agribusiness plays a vital role in economic and social development, especially in Africa and Europe. This thesis explores the opportunities and challenges in the agri-food sector and how collaboration between these regions can support sustainable agricultural growth. It focuses on key issues such as food security, job creation, and climate change, showing how joint efforts can build stronger, more competitive, and inclusive agricultural markets that benefit both regions. The research begins with a historical overview, explaining how traditional farming has evolved into today’s complex global systems. This helps highlight the importance of cooperation in overcoming current challenges. The study then focuses on Africa, examining difficulties such as limited access to quality seeds and fertilizers, outdated farming methods, poor infrastructure, and the effects of climate change. It also explores ways to modernize agriculture and promote sustainable development through improved policies and investment in local agribusiness. Technology plays a major role in this transformation. The thesis looks at innovations such as digital agriculture, precision farming, blockchain, and biotechnology, which can help increase productivity, reduce food waste, and encourage knowledge-sharing between Africa and Europe. It also discusses strategies to strengthen agricultural trade, including investing in infrastructure, aligning policies, providing financial support, and encouraging young people to engage in agri-tech businesses. This research offers practical solutions for policymakers, industry leaders, and researchers. By focusing on the benefits of collaboration, the thesis aims to show how Africa and Europe can work together to create a more sustainable, inclusive, and resilient agri-food system that supports economic growth, enhances food security, and tackles global challenges effectively.